Impact of tobacco smoking and alcohol consumption on the treatment efficacy among psoriasis patients: A study protocol - Fanlingzi Shen; Yuning Ding; Ruiping Wang (Tobacco Induced Diseases)
Psoriasis is a common skin disease. With an in-depth understanding of psoriasis, small-molecule drugs and biologics are developed and used in clinical practice, but some patients still cannot achieve a satisfactory therapeutic effect. Tobacco smoking and alcohol drinking are proven to be factors affecting psoriasis. Still, evidence of the impact of tobacco smoking and alcohol consumption on the efficacy of psoriasis treatment is limited. This study aims to understand the prevalence of tobacco smoking and alcohol drinking among patients with psoriasis in Shanghai and to examine the association between tobacco smoking as well as alcohol drinking and the therapeutic effect in patients with psoriasis. We conducted a longitudinal observational study and recruited at least 500 psoriasis patients at Shanghai Skin Disease Hospital. In this study, patients with clinically diagnosed psoriasis vulgaris, aged ≥18 years, both males and females, with informed consent were recruited. However, patients with pregnancy, serious underlying disease conditions, communication barriers, and violation of medication regulations were excluded. Patients with psoriasis in this study receive a physical examination and case record form interview. The primary outcome indicator is the proportion of patients with PASI 75 achievement at Week 8. In this study, we use SAS 9.2 software to analyze the data. This study has been reviewed and approved by the Institutional Ethics Review Committee of Shanghai Skin Disease Hospital in 2021 (NO. 2021-44). It has been registered in the Chinese Clinical Trial Registry (ChiCTR2200066403). Patient recruitment began in January 2021 and is proposed to be finished in December 2024. The findings in this study will provide evidence of how tobacco smoking and alcohol drinking impact the treatment efficacy among patients with psoriasis. Therefore, the implementation of tobacco control and alcohol abstinence benefit the improvement of treatment responses.